The Effect of the Vertical Dimension of Occlusion on Masticatory Efficiency in Edentulous Patients (Journal of Hama University, 2021)
Determining the Vertical Dimension of Occlusion (VDO) is a critical procedure in fabricating  complete dentures for edentulous patients. Studies indicate that the change in VDO affects the patient's biting force and may affect masticatory efficiency.Purpose: Evaluate the effect of the reduced VDO on masticatory efficiency in complete denture patients.Twenty completely edentulous subjects, 4 females and 16 males, their ages were between (40-70) years precipitated in this study. One upper and two lower complete  dentures were fabricated for each subject, the first set of upper and lower complete dentures were made with a suitable VDO, while the second set of complete dentures were made with reduced VDO (about 3 mm). The masticatory efficiency test was performed two months after the patient had delivered the first complete denture. The same procedures were repeated for the second set of complete denture wearers. The masticatory efficiency test was accomplished by multiple sieve method for both groups.the arithmetic mean of the masticatory efficiency results in the six sieves was in favor of the suitable VDO compared to the reduced VDO.The  arithmetic mean in the suitable VDO was)53.57 (%, while was (49.13%) in the reduced VDO group, But there were no significant differences in the comparison of the first five sieves, but significant differences were found in the comparison of the arithmetic means of the two groups in the  sixth sieve only.at the 95% confidence level.Conclusions: within the limits of the study there was no effect in the masticatory efficiency in conventional complete denture wearers when the VOD was reduced by approximately 3mm.